THINKING ON CHINESE CONTEMPORARY DESIGN EDUCATION--TAKING BAUHAUS AND ULM DESIGN EDUCATION AS EXAMPLES - Zhang JiaWei; Azwady Mustapha, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Designers require not just theoretical knowledge, but the practical skill to apply it. Consequently, the Bauhaus "twin-track approach" has been implemented in design education in China. Positive results have been obtained from the combination of theoretical education and practical experience. Design research in China primarily centred on the Bauhaus modular design in the 1980s. However, the advancement of society has posed various challenges to the Bauhaus and Ulm School of Design theories. Therefore, this paper analyses the design education concepts and modes utilised by Bauhaus and Ulm, to reflect on current design education in China and its obstacles.